A Java Programming Learning Assistant System Using Test-Driven Development Method - Funabiki, Nobuo; Matsushima, Yukiko; Nakanishi, Toru; Watanabe, Kan; Amano, Noriki (IAENG International Journal of Computer Science, 2013)
Recently, the object-oriented programming language Java has been used in many practical systems including enterprise servers, smart phones, and embedded systems, due to its high safety and portability. Thus, a lot of educational institutes have offered Java programming courses to foster Java engineers. In this paper, we propose a Web-based Java Programming Learning Assistant System (JPLAS) using the test-driven development (TDD) method, to enhance educational effects of Java programming by assisting self-studies of students who have studied the basic Java grammar while reducing teacher loads. In JPLAS, a teacher first registers a Java programming assignment with a statement, a model source code, and a test code. Then, a student writes a source code by reading the statement and the test code, such that the source code can be tested automatically at the server by using JUnit, a tool for the TDD method. We confirm the effectiveness of JPLAS through experimental applications to students in our department.